Remodeling of the chromatin landscape in peripheral blood cells in patients with severe Delta COVID-19 - Akimov, Vasiliy E.; Tychinin, Dmitriy I.; Antonova, Olga A.; Shaymardanov, Abusaid M.; Voronina, Maria D.; Deinichenko, Kseniia A.; Fateev, Oleg D.; Yudin, Vladimir S.; Yudin, Sergey M.; Mukhin, Vladimir E.; Romanova, Svetlana V.; Nekrasova, Aleksandra I.; et al. (Frontiers in Immunology, 2024)
COVID-19 is characterized by systemic proinflammatory shifts with development of serious alterations in the functioning of the immune system. Investigations of the gene expression changes accompanying infection state provide insight towards standing of the molecular and cellular processes depending on the sickness severity and virus variant. Severe Delta COVID-19 have been characterized by the appearance of the monocyte subset enriched for the proinflammatory gene expression signatures and shift of the ligand-receptor interactions. We profiled the chromatin accessibility landscape of 140,000 nuclei of the PBMC samples from healthy people or individuals with COVID-19. We investigated cis-regulatory elements and identified core transcription factors governing the gene expression state 1 in immune cells during COVID-19. For the severe cases we discovered that regulome and chromatin co-accessibility modules significantly altered across many cell types. Moreover, cases with the Delta variant are accompanied by specific monocyte subtype discovered with the scATAC-seq data. From our analysis follows that immune cells of individuals with severe Delta COVID-19 undergo significant remodeling of the chromatin accessibility landscape and development of the proinflammatory expression pattern. With a gene regulatory network modeling approach we investigated core transcription factors governing cell state and identified the most pronounced chromatin changes in CD14+ monocytes from individuals with severe Delta COVID-19. Together, our results provide novel insight into the cis-regulatory module organization and their impact on gene activity in immune cells during SARS-CoV-2 infection.